The lost innocence of ethanol: power, knowledge, discourse, and U.S. biofuel policy - Munro, Benjamin (Kansas State University, 2015)
In the United States, rationales for corn ethanol policies have included national energy security, air pollution abatement, clean technology development, and climate change mitigation. The ostensible benefits of corn ethanol have been used to justify the transfer of federal funds toward corn and ethanol production subsidies, consumption mandates, and import restrictions, plus substantial research and development efforts. Public and private sector funding has also focused on efforts to commercially develop biofuels from advanced technology using cellulosic biomass. Despite decades of public and commercial interest, cellulosic ethanol has failed to commercialize, corn ethanol remains heavily dependent on subsidies, and each of the alleged benefits of ethanol has been hotly disputed. This research examines the links between interest groups and rationales for biofuel policies. Drawing from Foucauldian discourse analysis, the research identifies key discourses supporting and opposed to biofuel development, and their relation to broader issues in environmental and energy politics. This approach involved a detailed review of newspaper archives, policy documents, Congressional bills, committee hearings and debates, governmental and non-governmental reports, and scientific research findings. It reveals how a powerful coalition of agricultural interests succeeded in harnessing biofuel discourses to popular public and political environmental and energy concerns. The primary discourses identified were Environmental Bureaucracy, Free Markets, Ecological Modernization, and Limits. A common element in the first three of these was Techno-Optimism. A Limits discourse opposed ethanol expansion, primarily based on a narrative of competition for agricultural land, and stood apart from other discourses in its mistrust of science and technology to resolve environmental problems. The research concludes that Foucauldian discourse analysis provides a useful tool for examining key shifts in policy debates, for clarifying the relationship between scientific knowledge and discursive power, for understanding divisions within environmental discourse, and for revealing the importance of scale in environmental public policy process.
Keywords: Biofuels; Corn; Ethanol Environmental Energy Policy; Environmental Studies (0477); Geography (0366); Political Science (0615)